Uma tipologia de fachada na igreja micaelense (1728-1882) - Vieira, M. A. R.; Sampaio, M. T. de.; Miranda, P. (ICEUBI2019 – International Congress on Engineering – “Engineering for Evolution”, 2020)
The religious spaces are carriers of great symbolic importance, standing out in the urban fabric not only for their location, but also for their scale in relation to the surrounding buildings. We show the relevance of the religious space in the S. Miguel island (Azores) urban fabric, where the church presents itself as an element of great importance. It is the generator of urban fabric, and it is usually strategically located as a landmark of the civic center of the localities. This study presents an analysis of the main facades of the parish churches of the island of S. Miguel built during the eighteenth and nineteenth centuries. It highlights the existence of a typology of facade, which is a consequence of the materials and building systems existing there at the time. This demonstration continues the studies carried out by Sousa (1986) with the concept of facade Micaelense baroque ornamentation and Caldas (2012) with the concept of Micaelense baroque facade and Micaelense type facade. Methodologically, the investigation was carried out through the analysis of the elements that make up the facades of the parish churches, the study of old and current photography, and drawings made in CAD; and the systematization of facades by grouping them into categories and establishing a typology between the various churches of the eighteenth and nineteenth centuries.